Editor’s Notes - Sindelar, Melanie Janet (Lidé města, 2025)
This issue explores how urban life is experienced, expressed, and imagined in times of profound transformation. Across different contexts, it examines what it means to belong to a city, how communities respond to crises through cultural expression, and why some people choose to leave urban environments in search of different lifestyles way of living. From singing and dancing as forms of solidarity and reflections on how cities might become more sustainable, connected, and accessible, the contributions in this issue trace the many ways people inhabit and shape urban spaces. Moving from Central Europe to the Global South, the authors offer grounded as well as imaginative perspectives on lived urbanity, resilience, and the evolving relationships between people and their cities.